STUDI KARAKTERISASI FISIOLOGI CENDAWAN ENTOMOPATOGEN Metarhizium spp DARI BERBAGAI RIZOSFER TANAMAN HORTIKULTURA KOTA PADANGSIDIMPUAN - Muhammad Agung Permadi; Amir Mahmud; Mukhlis Mukhlis; Rafiqah Amanda Lubis; Muhammad Tedi Faisal (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2020)
Entomopathogenic fungi are bioinsecticides used to control insect pests. Entomopathogenic fungi can found in the rhizosphere area of plants. This study aims to determine the germination, sporulation, and colonization of Metarhizium spp that are found in the various horticultural plants' rhizosphere of Padangsidimpuan. Metarhizium spp used were MetCP, MetKP, MetMP, MetKPP, MetSP, MetJP, MetTP. This research conducted in the Agrotechnology Laboratory of the Faculty of Agriculture, Universitas Muhmmadiyah Tapanuli Selatan. The study used a completely randomized design (CRD). The results showed that the highest germination rate at 6 hours after inoculation (HAI) founded in MetKPP of 31.05%. MetKPP also had the highest germination rate of 37.43% on 24 HAI. The highest diameter growth founded in MetKP, which was 5.50 cm at 14 HAI. The highest conidia density was 1,821 x 106 conidia/ml, found in MetMP, significantly different from MetCP, which had the lowest conidia density that was 1.169 x 106 conidia/ml.